Information management technologies in customer service management - A. N. Aleksakhin; S. A. Aleksakhina; M. A. Shoshin; V. A. Shumeiko (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Information flows in the digital economy are becoming a new type of assets of the organization. Information management solves two important tasks in the management of an organization: on the one hand, it coordinates information flow management activities, and on the other hand, it promotes the use of information technologies in making organizational and management decisions. Modern development of most market segments in conditions of increased competition for the client increases the relevance of research in the field of customer service management, including information management methods. Goal. The study aims to identify and generalize information management technologies that are advisable to use to improve the quality of client services.Materials and methods. The information and material basis for studying client service management technologies is the empirical base of Russian organizations, as well as analytical data from news agencies and websites. Generalization, analysis and interpretation of the obtained results were carried out using methods of a general scientific nature, as well as complex and empirical methods. Results and discussion. Management of customer services of the organization is the key to retaining customers and forming a loyal customer base. Modern information management technologies make it possible to make this process the highest quality and most efficient, quickly identifying customer preferences and contributing to the adaptation of current services to customer needs. As a result of the study, key directions for the use of information management technologies in improving the quality of the functioning of client services were formed. Conclusion. The generalization of theoretical and practical aspects of the development of information management technologies made it possible to develop a methodological apparatus for their use in the development of client services, which in the future will contribute to strengthening the competitive position of the organization based on increasing the loyalty of its client base.